Reforming public service provision: What have we learned? - Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2015)
The essay discusses some key features of the wawe of public sector reforms that has swept through the OECD area during the last three decades under the heading of New Public Management. I review what economic theory and the empirical evidence can say about the effects of introducing pay for performance, performance measurement and various forms of competition in the public sector. I also review some evidence on the growing bureaucratization of the public sector and discuss the drivers behind this trend. The final part of the essay draws some implications for the design of public sector reforms.
Keywords: 330